Elevated admission urinary N-acetyl-β-D-glucosamidase level is associated with worse long-term clinical outcomes in patients with acute heart failure. Issue 5 (1st August 2020) - Funabashi, Sayaka; Omote, Kazunori; Nagai, Toshiyuki; Honda, Yasuyuki; Nakano, Hiroki; Honda, Satoshi; Iwakami, Naotsugu; Hamatani, Yasuhiro; Nakai, Michikazu; Nishimura, Kunihiro; Asaumi, Yasuhide; Aiba, Takeshi; et al.
Abstract : Background: The prognostic significance of urinary N -acetyl-β-D-glucosamidase in acute heart failure has not been fully elucidated. Accordingly, this study investigated whether urinary N -acetyl-β-D-glucosamidase could be associated with subsequent adverse events in acute heart failure patients. Methods: We studied 708 consecutive acute heart failure patients who had accessible N -acetyl-β-D-glucosamidase data on admission from the National Cerebral and Cardiovascular Center Acute Decompensated Heart Failure registry. We assessed the relationship between the admission N -acetyl-β-D-glucosamidase level and the combined endpoint of all-cause death and worsening heart failure. Worsening heart failure was defined as worsening symptoms and signs of heart failure requiring intensification of intravenous therapy such as diuretics, vasodilators and inotropes or initiation of mechanical support after stabilisation with initial treatment during hospitalisation, or readmission due to heart failure after discharge. Results: During a median follow-up period of 763 (interquartile range 431–1028) days, higher urinary N -acetyl-β-D-glucosamidase was significantly related to increased events of all-cause death and worsening heart failure. In addition, patients with higher urinary N -acetyl-β-D-glucosamidase and lower estimated glomerular filtration rate on admission had the worst clinical outcomes. In multivariable Cox regression, urinary N -acetyl-β-D-glucosamidase on admission was independently associated with adverse events (hazard ratio 1.19, 95% confidence interval 1.04–1.35) even after adjustment by covariates including the baseline estimated glomerular filtration rate. Conclusions: Higher urinary N -acetyl-β-D-glucosamidase level on admission was independently associated with worse clinical outcomes. Our findings indicate the potential value of assessing urinary N -acetyl-β-D-glucosamidase on admission for further risk stratification in patients with acute heart failure.